NEW MARGINALS, OLD MARGINALS IN THE AGE OF COVID-19 IN INDONESIA - Anton Novenanto; Baswara Kristama; Yuni Kurniawaty; Lutfi Amiruddin; Fitri Widowati; Nuzul Solekhah; Laila Azkia; Erina Saputri; Syaiful Anam; Gadi Makitan; Palupi Pitakaningrum (LIPI Press, 2021)
This study is a patchwork ethnography of how certain social groups in Indonesia are marginalized while coping with the ongoing global pandemic of COVID-19. A consortium consisting of social researchers living in different locations in Indonesia conducted observation to identify marginal/marginalized groups in their surroundings. We focus on the marginalization or marginalizing process by considering the vulnerability concept developed within the disaster studies field. Our observations guided by questions: How vulnerable were pre-existing marginal/marginalized groups in Indonesia before and during the outbreak? To what extent does the Indonesian government approach for the outbreak become a new vulnerability structure by creating new marginal groups within the society? Our observation identified that the ongoing pandemic has further marginalized pre-existing marginal groups and emerged some new marginal groups within society.